Analisis Pengaruh Suku Bunga BI-Rate, Jumlah Uang Beredar M2, Dan Kurs Dollar As Terhadap Tingkat Inflasi Di Indonesia. - Khairul Akbar; Lya Novarian Nainggolan; Ahmad Albar Tanjung; Wahyu Ario Pratama; Ade Firmansyah Tanjung (Universitas Islam Sumatera Utara, 2023)
Inflation developments are a concernmain foreconomy in Indonesia. BI (Bank Indonesia) has a purposeuthe goals to maintain the stability of rupiah value which reflected in the inflation development.Unstable inflation is general and continuously increase in of price level of services and goods. It has an impact on weakening the purchasing power of the masses and then causes a decline in the national income of a country on a large scale. Therefore the rate of inflation is expected to be controlled. This study has a purpose to discuss the level of influence of BI- interest rate, money circulation, and the US Dollar Exchange Rate as an independent variable on Indonesian Inflation for the period 2005-2023 as the dependent variable used ECM-ADF(ADF error correction model). This study is retricted to analyze the secondary data with time series data between 2005-2023. The results showed that the variables Bir (Bi-rate), Jub (money supply), and Kurs (US Dollar Exchange Rate) have a significant effect on inflation in the short term. This means that an increase in interest rates, the amount of money in circulation and the exchange rate will increase inflation in Indonesia. While in the long run the variables Beer and Exchange Rate have a significant effect on inflation and only the variable Jub (money supply) has no significant effect on inflation. This means that an increase in money supply will reduce inflation in Indonesia.